Biostabilization Of Cafeteria Waste By Takakura Home Method - Gan, Huei Ying (2014)
experiment was designed to evaluate the degree of maturity and stability in the biostabilization of cafeteria waste using Takakura Home Method (THM). THM method was adapted from Kitakyushu International Techno-Cooperative Association (KITA). In the present study, three local fermented food products (tempeh, tempoyak and tapai pulut) were used as microbial starters. Tempeh was selected based on its predominance of fungal population. Fungi play a crucial role in the decomposition process due to its extensive network of mycelium to colonize the lignocellulose matrix in organic matter, and its high enzymatic capacities to decompose recalcitrant detritus materials. Tempoyak and tapai were used based on the presence of lactic acid bacteria (LAB) and yeast that suppres the growth of pathogens and enable the growth of thermophilic bacteria. There were four reactors with different microbial starters; (i) tempeh (T1), (ii) tempoyak (T2), (iii) tapai pulut (T3) and cow manure (control). Cafeteria waste was used as the feed material and biostabilization process was observed for 28 days. Findings indicated that the microbial growth of total bacteria (TB), total fungi (TF) and actinomycetes (AC) increased in the final stage of microbial seeding preparation in all four reactors and was the lowest in control. The maturity of the biostabilization process was evaluated using temperature, pH, elemental analysis of carbon, nitrogen and C:N. Highest temperatures for T1, T2, T3 and control were recorded at 43°C, 47.8°C, 45.3°C and 41°C respectively. Maturity of the biostabilization process was indicated by temperature changes and gradual decrease of temperature towards ambient temperature.